Valence compensated perovskite oxide system Ca1-xLaxTi1-xCrxO3. Part II: Electrical transport behavior - Dwivedi R.K.; Kumar D.; Parkash O. (My University, 2025)
Electrical transport behaviour of the valence compensated system Ca1-xLaxTi1-xCrxO3 (x ≤ 0.50) has been investigated by studying the Seebeck co-efficient, DC and AC conductivity as a function of temperature. Seebeck co-efficient, DC conductivity of different compositions has been measured in the temperature range 300 K-1000 K. AC conductivity for different compositions were determined in the temperature range 100-550 K and frequency range 10 Hz-10 MHz. Positive values of Seebeck co-efficient show that holes are the majority charge carriers. Conduction seems to occur by correlated barrier hopping of holes among Cr3+ and Cr4+ ions or Vo• and Vo••. Almost equal values of activation energies obtained for DC conductivity and dielectric relaxation process show that both the processes occur by the same mechanism. © 2001 Kluwer Academic Publishers.